Sarco/endoplasmic reticulum Ca(2+)-ATPase (SERCA) activity is required for V(D)J recombination - Chen, Chun-Chin (J Exp Med, 2021)
A whole-genome CRISPR/Cas9 screen identified ATP2A2, the gene encoding the Sarco/endoplasmic reticulum Ca(2+)-ATPase (SERCA) 2 protein, as being important for V(D)J recombination. SERCAs are ER transmembrane proteins that pump Ca(2+) from the cytosol into the ER lumen to maintain the ER Ca(2+) reservoir and regulate cytosolic Ca(2+)-dependent processes. In preB cells, loss of SERCA2 leads to reduced V(D)J recombination kinetics due to diminished RAG-mediated DNA cleavage. SERCA2 deficiency in B cells leads to increased expression of SERCA3, and combined loss of SERCA2 and SERCA3 results in decreased ER Ca(2+) levels, increased cytosolic Ca(2+) levels, reduction in RAG1 and RAG2 gene expression, and a profound block in V(D)J recombination. Mice with B cells deficient in SERCA2 and humans with Darier disease, caused by heterozygous ATP2A2 mutations, have reduced numbers of mature B cells. We conclude that SERCA proteins modulate intracellular Ca(2+) levels to regulate RAG1 and RAG2 gene expression and V(D)J recombination and that defects in SERCA functions cause lymphopenia.